PengaruhTeknologi Informasi, Kualitaas Pelayanan dan Keunggulan Terhadap Minat Generasi Milenial Menggunakan Mobile Banking di Bank Syariah - Cahyana, Divka Adella; Azwari, Peny Cahaya (Multidisciplinary Journal of Education , Economic and Culture, 2023)
This study aims to determine whether the relationship between Information Technology, Service Quality, Excellence to the interest of the Millennial Generation using Mobile Banking at Islamic Banks. This type of research is correlation research using a quantitative approach. The sample of this study was 50 respondents, namely students and customers who were registered as mobile banking users at Islamic banks. Data collection techniques using questionnaires. The data analysis method uses multiple linear regression tests, reliability tests, validity tests and hypothesis tests (F test and T test), then the data is processed using the SPSS application. This study suggests that the variables of information technology, service quality and excellence have a significant effect together (simultaneously) on the dependent variable, namely the interest of the millennial generation